Les services collectifs de transport intra-urbain à Bouaké : des offres de mobilité à hauts risques pour les populations - Kouakou Attien; Jean-Michel Konan (EchoGéo)
Bouaké, second city of Côte d’Ivoire after Abidjan has been experiencing an important and dynamic urbanization. In this running phenomenon, the non-attendance of a constant public transportation services such as autobuses engendered the birth of three modes of public transport. Minibuses, commonly known as gbakas and communal taxis appeared in after independence before then appeared in 2002 the bikes taxi, during the political and armed conflict. Despite, some permanent dangers such as the bad quality of the services and the vehicles linked to these types of mutual transport Bouaké’s citizens use them. For, they sometimes have no choice.